Long Non-Coding RNA LINC01569 Promotes Proliferation and Metastasis in Colorectal Cancer by miR-381-3p/RAP2A Axis - Ye, Guang-yao; Zhang, Zi-zhen; Zhu, Chun-chao; Cong, Zhi-jie; Cui, Zhe; Chen, Lu; Zhao, Gang (Frontiers in Oncology, 2021)
Abstract Background: Long non-coding RNAs (lncRNAs) display regulatory function flexibly in tumor onset and developments. Our study aimed to delve into the roles of lncRNA LINC01569(LINC01569) in colorectal cancer (CRC) progression to study the potential mechanisms. Methods: The genetic expression profiles of miR-381-3p and LINC01569 were measured by RT-PCR. The subcellular localization of LINC01569 in CRC cells was identified using Subcellular Fractionation Location. Loss-of-function assays were performed to explore the potential effects of LINC01569 on CRC progression. Dual-luciferase reporter analysis was employed to verify the binding connections among LINC01569, miR-381-3p and RAP2A. Results: LINC01569 expression was distinctly increased in CRC. Curiously, if LINC01569 is removed, CRC cells won’t migrate, proliferate, and invade remarkably. Molecular mechanism exploration uncovered that LINC01569 acted as a ceRNA competing with RAP2A to bind with miR-381-3p. Furthermore, rescue experiments corroborated the fact that miR-381-3p suppression reversed the inhibitory actions of LINC01569 knockdown on the expression of RAP2A and CRC progression. Conclusion: Overall, our findings indicate that LINC01569 plays a key role in CRC development by means of aiming at the miR-381-3p/RAP2A axis and can be equivalent to an underlying medicinal target to save CRC patients.